2015
DOI: 10.1371/journal.pone.0143609
|View full text |Cite
|
Sign up to set email alerts
|

Impact of specific training and competition on myocardial structure and function in different age ranges of male handball players

Abstract: Handball activity involves cardiac changes and demands a mixture of both eccentric and concentric remodeling within the heart. This study seeks to explore heart performance and cardiac remodeling likely to define cardiac parameters which influence specific performance in male handball players across different age ranges. Forty three players, with a regular training and competitive background in handball separated into three groups aged on average 11.78±0.41 for youth players aka “schools”, “elite juniors” 15.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Similarly, a study in which participants were divided into groups according to training hours per week reported that IVS thickness, end-diastolic diameter, and left ventricular mass were significantly higher in athletes whose training exceeded 8 h/week than in controls [22]. Agrebi et al reported that among children who were having a regular training for handball, LVEDd, LVESd, LA, AR, and LV mass are all significantly lower in younger children than in older ones and adults [23]. This finding was suggested to be associated with the duration of prior practice and early cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study in which participants were divided into groups according to training hours per week reported that IVS thickness, end-diastolic diameter, and left ventricular mass were significantly higher in athletes whose training exceeded 8 h/week than in controls [22]. Agrebi et al reported that among children who were having a regular training for handball, LVEDd, LVESd, LA, AR, and LV mass are all significantly lower in younger children than in older ones and adults [23]. This finding was suggested to be associated with the duration of prior practice and early cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…(2016) reported an increment in right ventricular size parameters during active training with no significant changes in functional echocardiographic parameters. Finally, aortic root size showed an increment related to the athlete's age (Agrebi, Tkatchuk, Hlila, Mouelhi, & Belhani, 2015) and probably not a consequence of exercise training.…”
Section: Athlete's Heartmentioning
confidence: 99%
“…The results of the reviewed studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] are presented in Tables 1-3.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported that male athletes met the diagnostic criteria for LVH more frequently [14,17]; one recorded RVH as less common than LVH [17]. One study showed that the duration of the PR interval increases with age but remains within normal limits [16]. Finocchiaro et al [14] found that 4% of the participants presented a left-axis deviation, and 33% of the male athletes they studied had a QRS duration >100ms.…”
Section: Electrocardiographic Modificationsmentioning
confidence: 99%
See 1 more Smart Citation